2016
DOI: 10.1128/iai.01308-15
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of an Skp-Like Protein, PGN_0300, in the Type IX Secretion System of Porphyromonas gingivalis

Abstract: The oral Gram-negative anaerobic bacterium Porphyromonas gingivalis is an important pathogen involved in chronic periodontitis. Among its virulence factors, the major extracellular proteinases, Arg-gingipain and Lys-gingipain, are of interest given their abilities to degrade host proteins and process other virulence factors. Gingipains possess C-terminal domains (CTDs) and are translocated to the cell surface or into the extracellular milieu by the type IX secretion system (T9SS). Gingipains contribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 68 publications
(88 reference statements)
4
41
0
Order By: Relevance
“…When the same proteins were detectable in the growth medium of the wild-type strain, they had much lower Mascot scores and no peptides corresponding to their respective CTDs. This “leaky” OM phenotype, which leads to release of non-cleaved CTDs from CTD-cargo proteins, is similar to that reported by Taguchi et al 36. These authors reported that the chaperone Skp-like protein (PGN_0300) is required for OM insertion of PorU sortase, which in turn is necessary for CTD cleavage from CTD-cargo proteins.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…When the same proteins were detectable in the growth medium of the wild-type strain, they had much lower Mascot scores and no peptides corresponding to their respective CTDs. This “leaky” OM phenotype, which leads to release of non-cleaved CTDs from CTD-cargo proteins, is similar to that reported by Taguchi et al 36. These authors reported that the chaperone Skp-like protein (PGN_0300) is required for OM insertion of PorU sortase, which in turn is necessary for CTD cleavage from CTD-cargo proteins.…”
Section: Resultssupporting
confidence: 86%
“…These authors reported that the chaperone Skp-like protein (PGN_0300) is required for OM insertion of PorU sortase, which in turn is necessary for CTD cleavage from CTD-cargo proteins. Consistently, deletion of PGN_0300 resulted in failure of PorU insertion and, thus, T9SS function36.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…PG0534 is a predicted TonB-dependent receptor shown to be located in the outer membrane and required for T9SS function but it's specific role has not been determined (Saiki and Konishi, 2010a). A Skp-like protein, PGN_0300 has also been proposed to be involved in the T9SS (Taguchi et al, 2015). Since Skp is known in other species to be involved in the assembly of outer membrane proteins (Noinaj et al, 2017), it remains to be demonstrated that PGN_0300 is specific to the T9SS, rather than simply performing its expected role of assembling certain outer membrane proteins including one or more components of the T9SS.…”
Section: Other Components Of the T9ssmentioning
confidence: 99%
“…A-LPS is a phosphorylated branched mannan [67], that is attached to many proteins translocated through the type IX secretion system (T9SS), thus anchoring them to the bacterial surface [68]. A mutant unable to incorporate A-LPS into T9SS substrates is less virulent in a mouse subcutaneous infection model [69] Gingipains are yet another important aspect of P. gingivalis virulence. These enzymes play important roles in bacterial housekeeping and infection.…”
Section: Porphyromonas Gingivalismentioning
confidence: 99%